Problematika Badan Layanan Umum Daerah Pusat Kesehatan Masyarakat - Sakti, Eklamsia; Sari Maduratna, Enggal; Firdaus, Nailufar (NHM PRESS, 2024)
This study aims to explore the problems of Community Health Centers (Puskesmas) when undergoing a status transition to a Regional Public Service Agency (BLUD). Since Regulation of the Minister of Home Affairs No. 79/2018 on Regional Public Service Agency (BLUD) was officially implemented, the Puskesmas has changed its status to BLUD. When this transition occurs, many problems are faced by the Puskesmas. Therefore, researchers conducted a case study at the Bangkalan Health Center regarding the problems of becoming a BLUD. The resource persons were the Head of the TU Sub-Department, PJ UKM, UKP, Pharmacy and Laboratory, Nursing, Midwives, and Public Health with the Small Discussion Group (SGD) system. The results of the search found that Puskesmas Bangakaln has problems in financial management, human resources who are only experts in the field of health, technology that is still locked, jammed National Health Insurance (JKN) capitation funds, and has not formed an Internal Supervisory Unit (SPI).